Factors Affecting the Academic and Cultural Adjustment of Saudi International Students in Australian Universities - Alsahafi, Nisreen; Shin, Seong-Chul (Journal of International Students, 2017)
The authors investigate factors affecting Saudi students’ educational experiences in Australian universities and their adjustment issues. The data comes from the survey of 100 Saudi international students in Sydney and subsequent interviews. The analysis revealed that language proficiency is the main barrier to Saudi students’ academic and social adjustment, with some academic factors such as classroom activities and assessment methods, and social factors such as homesickness and loneliness also affecting their study. The analysis also identifies Saudi students’ coping strategies such as improvement of language competence, time management and mixing with others. It then discusses differences in perceived level of difficulty with respect to gender, age, educational level and length of residence, as well as some implications of the findings.